Computational Fluid Dynamics (Cfd) Simulation Of Low Renolds Number Flow Over Airfoils For Unmanned Aerial Vehicle (Uav) - Chan, Quan Xin (Universiti Sains Malaysia, 2019)
The technology of Unmanned Aerial Vehicle (UAV) or commonly known as drone technology is growing fast and rapidly advancing in Malaysia. The growth in this technology is due to an increase of UAV uses for many tasks. In the military field, the UAV is usually used to carry out surveillance mission or even as a combat fighter. Apart from military applications, the UAV is widely involved for research like sending UAV to a hard-to-reach terrain to collect data that is difficult to obtain. Hence, it leads to a growing interest in research of UAV to build a better UAV. A good UAV is normally accompanied with some of the features such as equipped with high payload, shortened take-off and landing distances, lower stall speed and a high lift airfoil with low Re number. Thus, the project focuses on the high lift airfoil with low Re to have a lower stall speed as well as a large enough of lift produced. Two cambered airfoils will be chosen for aerodynamic analysis with Re number lower than 100,000. The limitation of Re number is to ensure the air flow over the airfoils are fully laminar. The analysis is conducted using computational fluid dynamics simulation software which is Fluent. A 2D geometry is first plot using Design Modeler. Meshing is generated for each airfoil after import from Design Modeler. The meshing is then read into Fluent to perform simulation and the result such as graph of lift coefficient at different AOA and graph of drag coefficient at different AOA are used to compare the aerodynamic characteristics of each airfoil.